Marketing research - Hair, Joseph F.; Lukas, Bryan A.; Miller, Kenneth E. (McGraw Hill, 2012)
Marketing Research, 3/e takes an application-oriented approach, providing students with the tools and skills necessary to solve business problems and exploit business opportunities. This new edition was written to meet the needs of students through additional coverage of qualitative methods, emphasis on applied research projects as well as cases studies or exercises at the end of the chapters. The text is concise, highly readable and value-priced, yet it delivers the basic knowledge needed for an introductory text. The authors provide the student with an exciting, up-to-date text and an extensive supplement package